2022
DOI: 10.3389/fpls.2022.865048
|View full text |Cite
|
Sign up to set email alerts
|

Nanofertilizer Possibilities for Healthy Soil, Water, and Food in Future: An Overview

Abstract: Conventional fertilizers and pesticides are not sustainable for multiple reasons, including high delivery and usage inefficiency, considerable energy, and water inputs with adverse impact on the agroecosystem. Achieving and maintaining optimal food security is a global task that initiates agricultural approaches to be revolutionized effectively on time, as adversities in climate change, population growth, and loss of arable land may increase. Recent approaches based on nanotechnology may improve in vivo nutrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 68 publications
(45 citation statements)
references
References 188 publications
1
44
0
Order By: Relevance
“…The farmers regularly use pesticides and synthetic fertilizers to enhance crop production, which impose threat to the agricultural ecosystem. However, this approach may assist plant performance/fitness for crop improvement, fruit and grain quality (Verma et al, 2022a;Wang et al, 2022) during adverse environmental conditions. It is an emerging interdisciplinary area potentially promoting plant growth and stress tolerance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The farmers regularly use pesticides and synthetic fertilizers to enhance crop production, which impose threat to the agricultural ecosystem. However, this approach may assist plant performance/fitness for crop improvement, fruit and grain quality (Verma et al, 2022a;Wang et al, 2022) during adverse environmental conditions. It is an emerging interdisciplinary area potentially promoting plant growth and stress tolerance.…”
Section: Introductionmentioning
confidence: 99%
“…The recent investigations indicated that the fertilization of soil with nSi stimulates photosynthetic CO 2 assimilation rate, biochemical and molecular responses in plants that resist unfavorable environmental conditions (Verma et al, 2022a). Abiotic stresses induce the generation of reactive oxygen species (ROS), i.e., singlet oxygen, superoxide, hydrogen peroxide, and hydroxyl radicals in cells (Das and Roychoudhury, 2014;Kim et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Various reports demonstrated the efficiency of ENPs in agriculture ( Manjunatha et al., 2016 ; Adisa et al., 2019 ; Verma et al., 2022a ; Verma et al., 2022b ). However, the majority of earlier investigations on the interactions between plants and ENPs concentrated on the possible toxicity of nanoparticles to higher plants.…”
Section: Defense Mechanism Against Ros Generationmentioning
confidence: 99%
“…The minimal oxidative damage indices that followed rehydrating plants with nSi indicated its major role in scavenging excessive ROS and activating antioxidant defense mechanisms in plants during drought. The excess level of ROS could be due to decreased CAT activity during unfavorable environmental variables ( Chahardoli et al., 2020 ; Verma et al., 2022a ; Verma et al., 2022b ). The enhanced CAT activity in the plants associated with nSi reveals an enhancement in the ROS-scavenging capacity of stressed plants, which is accompanied by plant protection/production from oxidative damage.…”
Section: Nanosilicon and Ros Action Of Mechanism In Response To Water...mentioning
confidence: 99%
See 1 more Smart Citation